Pelatihan Menjahit Vest dan Obi Sebagai Bentuk Penguatan Vokasi Bagi Siswa SLB - Fransiska Intan Permata Sari; Agiska Shinta Safiyana; Yulianto (Institut Seni Indonesia Surakarta, 2025)
This community service activity was carried out at SLB Negeri Sragen as part of the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) program. The main challenge faced by the partner was the lack of instructors with specific skills in sewing, which resulted in students not receiving adequate vocational training, especially in making vests and obi belts. The aim of this activity was to improve the vocational skills of students with special needs through hands-on sewing training using a non-exclusive and adaptive method. The approach used was a participatory method, where students were actively involved in the learning process, from the introduction of sewing tools and pattern cutting to the completion of wearable products. University students acted as facilitators in an interactive and systematic knowledge-sharing process. The outcomes of this program included wearable vest and obi products, as well as the creation of a digital catalog showcasing the students’ work. This activity demonstrated that an appropriate vocational approach can significantly enhance the independence and capabilities of SLB students. Keywords: MBKM, vocational education, students with special needs, participatory method, transfer of knowledge.